Realizacja funkcji perswazyjnej w Palmie panieńskiej benedyktyna Basilia Gradiego w przekładzie jezuity Szymona Wysockiego - Kaczor-Scheitler, Katarzyna (Załącznik Kulturoznawczy, 2018)
The material basis of the article is Palma panieńska albo rozprawa o stanie dziewiczym [Virginal Palm or a Treatise on the Virginal State] (Kalisz 1607) as translated by Szymon Wysocki, who faithfully rendered into Polish an Italian work Trattato della verginita et dello stato verginale (Rome 1584) by Basilio Gradi. The article demonstrates that the translation should be associated with the rhetorical culture of the society of the time and analysed as a persuasive text. The paper clarifies that the inventio layer of the work remains in a close connection with dispositio and elocutio. It offers an insight into diversified sources of arguments (references to the biblical tradition, patristic tradition and monastic legislation) as a form of persuasion (inventio), which are supposed to cause changes or reinforce beliefs in the public and motivate them to behave in a specific way. In the range of elocutio the verbal forms of affecting the public are presented, which impel them to take a clearly specified position (in terms of message) and to undertake a specific action. The reflection includes also the remarks about the significance of a communicative function based on appeal-like statements of a recommendatory, warning or admonitory nature.